P-436 EndoTime: Non-categorical timing estimates for luteal endometrium. (30th June 2022) - Mitchell, A; Lipecki, J; Muter, J; Lucas, E; Makwana, K; Fishwick, K; Odendaal, J; Hawkes, A; Vrljicak, P; Brosens, J; Ott, S
Abstract: Study question: Can expression measurements of a small panel of genes be used to develop a continuous, non-categorical model for the improvement of endometrial biopsy timing accuracy? Summary answer: Measuring expression levels of six genes ( IL2RB, IGFBP1, CXCL14, DPP4, GPX3, and SLC15A2 ) is sufficient to obtain and assess substantially more accurate timing estimates. What is known already: Commercially available endometrial timing approaches based on gene expression require much larger gene sets and use a categorical approach that classifies samples as pre-receptive, receptive, or post-receptive. Study design, size, duration: Gene expression was measured by RT-qPCR in different sample sets, comprising a total of 664 endometrial biopsies obtained 4 to 12 days after a self-reported positive home ovulation test. A further 36 endometrial samples were profiled by RT-qPCR as well as RNA-sequencing. Participants/materials, setting, methods: A computational procedure, named 'EndoTime', was established that models the temporal profile of each gene and estimates the timing of each sample. Iterating these steps, temporal profiles are gradually refined as sample timings are being updated, and confidence in timing estimates is increased. After convergence, the method reports updated timing estimates for each sample while preserving the overall distribution of time points. Main results and the role of chance: The Wilcoxon rank-sum test was used to confirm that ordering samples by EndoTime estimates yields sharper temporal expression profiles for held-out genes (not used when determining sample timings) than ordering the same expression values by patient-reported times ( GPX3 : p < 0.005; CXCL14 : p < 2.7e-6; DPP4 : p < 3.7e-13). Pearson correlation between EndoTime estimates for the same sample set but based on RT-qPCR or RNA-sequencing data showed high degree of congruency between the two ( p  = 8.6e-10, R-squared = 0.687). Estimated timings did not differ significantly between control subjects and patients with recurrent pregnancy loss or recurrent implantation failure ( p > 0.05). Limitations, reasons for caution: Timing estimates are informed by glandular gene expression and will only represent the temporal state of other endometrial cell types if in synchrony with the epithelium. Additionally, methods that estimate the day of ovulation are still required as these data are essential inputs in our method. Wider implications of the findings: Our method is the first to assay the temporal state of endometrial samples on a continuous domain, enabling accurate temporal profiling of any gene in luteal phase biopsies for a wide range of research applications and, potentially, clinical use. It is freely available, open-source software including supporting data sets. Trial registration number: Not applicable